Klasifikasi Kualitas Beras berdasarkan Nilai Data Larik Sensor Gas MQ menggunakan Metode Jaringan Syaraf Tiruan berbasis Arduino - Defri Alif Raihan; Dahnial Syauqy; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Rice is the result of the rice plant which is separated from the husks, every year the need of rice for indonesian people continues to increase, the abundant rice yields make rice have different types and qualities, in general the components that make up the smell of rice consist of several compounds it will produce a different smell of rice. Indonesian people still use conventional methods to classify quality in terms of taste and aroma, this makes the quality classification inaccurate and produces inappropriate quality, that makes many people commit fraud by circulating unsuitable types of rice and make bad quality which causes losses to various parties due to inappropriate prices and quality. With the development of technology, a tool that can classify based on quality is made using input from the array of MQ gas sensor by utilizing the Arduino UNO R3 microcontroller as a data processor from the gas sensor and utilizing a computational time code which make the system can classify quickly, the classification process uses the artificial neural network method and the classification results will be displayed on a 16x2 I2C LCD. the system is able to classify the quality with an average execution time of 54 milliseconds. From 11 test, the system is able to complete 9 times the output according to the detected sample which makes the accuracy of the system more than 80% and in accordance with which is expected.